Zanubrutinib versus bendamustine and rituximab in untreated chronic lymphocytic leukaemia and small lymphocytic lymphoma (SEQUOIA): a randomised, controlled, phase 3 trial. Issue 8 (August 2022) - Tam, Constantine S; Brown, Jennifer R; Kahl, Brad S; Ghia, Paolo; Giannopoulos, Krzysztof; Jurczak, Wojciech; Šimkovič, Martin; Shadman, Mazyar; Österborg, Anders; Laurenti, Luca; Walker, Patricia; Opat, Stephen; et al.
Summary: Background: Zanubrutinib is a next-generation, selective Bruton tyrosine kinase inhibitor with efficacy in relapsed chronic lymphocytic leukemia (CLL) and small lymphocytic lymphoma (SLL). We compared zanubrutinib with bendamustine–rituximab to determine its effectiveness as frontline therapy in patients with CLL or SLL. Methods: We conducted an open-label, multicentre, phase 3 study at 153 academic or community hospitals in 14 countries and regions. Eligible patients had untreated CLL or SLL requiring treatment as per International Workshop on CLL criteria; were aged 65 years or older, or 18 years or older and had comorbidities; and had an Eastern Cooperative Oncology Group performance status score of 0–2. A central interactive web response system randomly assigned patients without del(17)(p13·1) to zanubrutinib (group A) or bendamustine–rituximab (group B) by sequential block method (permutated blocks with a random block size of four). Patients with del(17)(p13·1) were enrolled in group C and received zanubrutinib. Zanubrutinib was administered orally at 160 mg twice per day (28-day cycles); bendamustine at 90 mg/m 2 of body surface area on days 1 and 2 for six cycles plus rituximab at 375 mg/m 2 of body surface area the day before or on day 1 of cycle 1, and 500 mg/m 2 of body surface area on day 1 of cycles 2–6, were administered intravenously. The primary endpoint was progression-free survival per independent review committee in the intention-to-treat population in groups A and B, with minimum two-sided α of 0·05 for superiority. Safety was analysed in all patients who received at least one dose of study treatment. The study is registered with ClinicalTrials.gov, NCT03336333, and is closed to recruitment. Findings: Between Oct 31, 2017, and July 22, 2019, 590 patients were enrolled; patients without del(17)(p13·1) were randomly assigned to zanubrutinib (group A; n=241) or bendamustine–rituximab (group B; n=238). At median follow-up of 26·2 months (IQR 23·7–29·6), median progression-free survival per independent review committee was not reached in either group (group A 95% CI not estimable [NE] to NE; group B 28·1 months to NE). Progression-free survival was significantly improved in group A versus group B (HR 0·42 [95% CI 0·28 to 0·63]; two-sided p<0·0001). The most common grade 3 or worse adverse event was neutropenia (27 [11%] of 240 patients in group A, 116 [51%] of 227 in group B, and 17 [15%] of 111 patients in group C). Serious adverse events occurred in 88 (37%) of 240 patients in group A, 113 (50%) of 227 patients in group B, and 45 (41%) of 111 patients in group C. Adverse events leading to death occurred in 11 (5%) of 240 patients in group A, 12 (5%) of 227 patients in group B, and three (3%) of 111 patients in group C, most commonly due to COVID-19 (four [2%] of 240 patients in group A), diarrhoea, and aspiration pneumonia (two each [1%] of 227 patients in group B). Interpretation: Zanubrutinib significantly improved progression-free survival versus bendamustine–rituximab, with an acceptable safety profile consistent with previous studies. These data support zanubrutinib as a potential new treatment option for untreated CLL and SLL. Funding: BeiGene.